My pony - Jeffers, Susan (New York : Hyperion Books for Children, 2004)
Longing to own a pony, a young girl finds that the one she draws seems to come alive and take her on a fantastic journey.
G3
Keywords: Ponies -- Fiction; Imagination -- Fiction; Drawing -- Fiction